Implementation and outcomes of telephone disclosure of clinical BRCA1/2 test results - Patrick-Miller, Linda (2013)
OBJECTIVES: With an increasing demand for genetic services, effective and efficient delivery models for genetic testing are needed. METHODS: In this prospective single-arm communication study, participants received clinical BRCA1/2 results by telephone with a genetic counselor and completed surveys at baseline, after telephone disclosure (TD) and after in-person clinical follow-up. RESULTS: Sixty percent of women agreed to participate; 73% of decliners preferred in-person communication. Anxiety decreased from baseline to post-TD (p = 0.03) and satisfaction increased (p < 0.01). Knowledge did not change significantly from baseline to post-TD, but was higher post-clinical follow-up (p = 0.04). Cancer patients had greater declines in state anxiety and African-American participants reported less increase in satisfaction. 28% of participants did not return for in-person clinical follow-up, particularly those with less formal education, and higher post-disclosure anxiety and depression (p < 0.01). CONCLUSIONS: Telephone disclosure of BRCA1/2 test results may not be associated with negative cognitive and affective responses among willing patients, although some subgroups may experience less favorable responses. Some patients do not return for in-person clinical follow-up and longitudinal outcomes are unknown. PRACTICE IMPLICATIONS: Further evaluation of longitudinal outcomes of telephone disclosure and differences among subgroups can inform how to best incorporate telephone communication into delivery of genetic services.